PELATIHAN MANAJEMEN KEPEMIMPINAN (LEADERSHIP) DALAM BERORGANISASI - Khodijah, Rahmawati; Putra, Purnama (LPPM Universitas Islam 45 Bekasi, 2020)
Leadership is an inherent ability in a person who leads and depends on various factors, both internal and external factors. Currently the problem of leadership is an urgent problem so that the phenomenon of a leadership crisis that occurs as a result of a crisis of confidence has emerged. One solution that can be put forward is to create capable individuals to become leaders. The method used in carrying out this activity is to conduct training for student council in building leadership in an organization. The Leadership Management Training Program (Leadership) in Organizations that has been implemented is a training where members of the Organization, especially the Intra School Student Organization (OSIS) at SMPN 18 Bekasi City can acquire and learn attitudes, abilities, expertise, specific behavioral knowledge related to organization and management leadership. This training is a series of activities designed to increase the skills, knowledge, experience, or changes in the attitudes of members of the Organization